Review the status of dental health and oral hygiene for young adult in Vietnam and in some countries - Do Chan Quang Anh; M. K. Makeeva; Yu. V. Shevelyuk (Эндодонтия Today, 2022)
At the age of 18 to 25, independent life begins, when most young people face the first difficulties of life, and in this age the issue of caring for oral hygiene fades into the background.Review the literature to identify the overall status of dental health and oral hygiene for young adult in Vietnam between other countries. Research results: Articles analyzed based on Pubmed, Medline, Web of Science, Scopus and Embase platforms (Key words: young adult, oral health status, decay, periodont; Numbers Russian research: 35, numbers foreigner research: 32). In some countries, insufficient attention has yet been paid to the status of dental health and the state of oral hygiene among young adult in the age group from 18 to 25 years. To prevent the deterioration of the dental health of the general population as a whole, measures of sanitary and educational work are needed, as well as constant monitoring of the state of dental health among young adult. Poor oral hygiene can lead to the development of carious and periodontal diseases among young adult.